2013
DOI: 10.1186/1472-6882-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of chewing stick miswak Salvadora persica

Abstract: BackgroundChewing stick (miswak Salvadora persica L.) is an effective tool for oral hygiene. It possessed various biological properties including significant antibacterial and anti-fungal effects. In the present study, we evaluated the antioxidant compounds in miswak.MethodMiswak root was extracted with 80% methanol. Methanol extract as antioxidant was evaluated by using DPPH, ABTS and phosphomolybdenum complex assays and analysis by GC-MS. Peroxidase, catalase and polyphenoloxidase assays were performed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Our findings of herbal extracts affectivity against oral pathogens are in consistence with previous reports [7, 8, 27]. Al-Obaida and coauthors declared miswak as an effective oral hygienic tool and found it helpful against different organisms causing oral cavity infections [28, 29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of herbal extracts affectivity against oral pathogens are in consistence with previous reports [7, 8, 27]. Al-Obaida and coauthors declared miswak as an effective oral hygienic tool and found it helpful against different organisms causing oral cavity infections [28, 29].…”
Section: Discussionsupporting
confidence: 91%
“…In 2013 Bafti et al reported Miswak extracts contain good antifungal properties [3]. Finding of our study also suggest Miswak as an antioxidant agent it contain antioxidant compounds for example peroxidase, catalase and polyphenol oxidase representing it as a good chewing stick [7]. …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Traditionally all parts of S. persica could be used for many medicinal purposes because of its high content of different secondary metabolites that could be used in the treatment against bacterial and fungal infections and have wide range of health care properties (Arora and Gupta, 2011;Sher et al, 2011;Mohamed and Khan, 2013;Gupta et al, 2015;Kumari and Parida, 2016). In the current study, the studied habitats affect the secondary metabolites composition of S. persica roots extract.…”
Section: Discussionmentioning
confidence: 99%
“…β-Sitosterol, manisic acid, and salvadourea [1,3-bis-(3-methoxybenzyl)-urea] were isolated from the root by Ray et al (1975). 2-Furancarboxaldehyde-5-(hydroxymethyl), furan-2-carboxylic acid-3-methyl-trimethylsilyl ester, and D-erythropentofuranose-2-deoxy-1,3,5-tris-O-(trimethylsilyl) were identified in root methanol extracts; these components exhibit antioxidant activities (Mohamed and Khan 2013). Stem essential oils include 1,8-cineole (eucalyptol), α-caryophellene, β-pinene, and 9-epi-(E)-caryophellene as the major components (Alali et al 2004).…”
Section: Introductionmentioning
confidence: 99%